'When the Most Blessed Athanasius was Opposing the Arians' ( Ep. 148.2.10): The Defense of the Nicene Faith Refracted through an Augustinian Lens - Bucur, Bogdan Gabriel (2024)
In a short passage in his Ep. 148, Augustine states that, in defense of the Nicene faith, Athanasius had argued that God allows himself to be seen in biblical theophanies 'by assuming a creature'. The article shows that this view is a distortion of Athanasius’ polemical strategies against Arianism, and that, in an effort to establish the credibility of his views, Augustine was, in fact, 'manufacturing' his famous predecessors’ consent to a fundamentally novel conception of visio Dei.